A JURIDICAL ANALYSIS OF THE IMPLEMENTATION OF THE REGENT OF CENTRAL LAMPUNG REGULATION NUMBER 56 OF 2022 IN CARRYING OUT THE DUTIES AND FUNCTIONS OF THE PROTOCOL AND LEADERSHIP COMMUNICATION DIVISION OF THE REGIONAL SECRETARIAT OF CENTRAL LAMPUNG REGENCY - Agus Muhammad Septiana; Riani Esrah Arisa Sagala (RADJA PUBLIKA, 2026)
The implementation of regional government policies is an essential aspect of achieving effective governance, including the administration of protocol duties and functions. This study aims to analyze the implementation of the Regent of Central Lampung Regulation Number 56 of 2022 concerning the Detailed Duties and Functions of Structural Positions and Functional Groups within the Regional Secretariat of Central Lampung Regency in carrying out the duties and functions of the Protocol and Leadership Communication Division, as well as to identify the factors hindering its implementation. This research employed both normative juridical and empirical juridical approaches. Data were collected through library research and field research by conducting interviews with the Head of the Protocol and Leadership Communication Division, the Head of the Protocol Subdivision, and staff members of the Protocol and Leadership Communication Division of the Regional Secretariat of Central Lampung Regency. The data were analyzed using a qualitative juridical approach by examining statutory regulations, administrative law theories, and empirical findings obtained from the field. The results indicate that the implementation of the Regent of Central Lampung Regulation Number 56 of 2022 within the Protocol and Leadership Communication Division has been carried out effectively, although it has not yet reached an optimal level. The implementation of protocol duties and functions has been conducted in accordance with the applicable regulations through the management of seating arrangements, event procedures, official honors, coordination of leadership activities, leadership communication, and documentation of governmental activities. Nevertheless, the implementation continues to face several obstacles arising from internal factors, including limited human resources, inadequate facilities and infrastructure, operational funding constraints, and organizational integrity, as well as external factors such as technological developments, regulatory changes, and regional fiscal conditions. Therefore, strengthening institutional capacity, optimizing organizational resources, and enhancing inter-agency coordination are necessary to improve the effectiveness of the implementation of the Regent of Central Lampung Regulation Number 56 of 2022 in supporting regional governance.